Hubungan Aktivitas Fisik dan Durasi Tidur Dengan Status Gizi pada Remaja di SMA Negeri 7 Bandar Lampung Tahun 2024 - Pradinda, Audia; Asustuti, Dewi Woro; Puteri, Hidayatusy Syukrina (Journal of Citizen Research and Development, 2024)
According to the Indonesian Health Survey (2023), the prevalence data on nutritional status (BMI/U) in children aged 16-18 years consists of very thin 1.8%, thin 5.5%, Normal 84.5%, Overweight 6.4%, Obese 1.8% (SKI, 2023). Bandar Lampung City has a high prevalence of obesity in adolescents. Of the 10 districts in Lampung Province, 3 of them have high obesity problems with a prevalence above 10%, namely: West Lampung Regency 10.3% Bandar Lampung City 11.1% and Metro City 9.9%. The purpose of this study was to determine the relationship between physical activity and sleep duration with nutritional status in adolescents at State Senior High School 7 Bandar Lampung. This type of research uses the Descriptive Analytical method with a Cross-Sectional approach. The population of this study was all 90 students of class XI IPS at State Senior High School 7 Bandar Lampung. The sampling technique used the random sampling method with a total sample of 82 respondents. The results of the study showed the effect of physical activity on nutritional status with a p-value of 0.024 and no effect of sleep duration on nutritional status with a p-value of 0.908. It is hoped that students will be able to know the knowledge related to the relationship between physical activity and sleep duration on one nutrient so that it can be a positive encouragement in implementing healthy lifestyle habits.